EDUCATIONAL PRACTICES AND INTELLECTUAL CULTURE OF THE NORTH CAUCASIAN INDIGENOUS POPULATION WITHIN THE CONTEXT OF IMPERIAL MODERNIZATION (SCHOOLING QUESTION AT THE MEETINGS OF ENTRUSTED DEPUTIES OF THE NALCHIK DISTRICT IN THE LAST THIRD OF THE 19th – EARLY 20th CENTURIES) - D. N. PRASOLOV (Кавказология, 2019)
Congress of entrusted – an original institution of district self-government of Kabardinians and Balkars, regularly functioning under the control of the Russian administration in the last third of the 19th – beginning of the 20th centuries. Representatives of rural societies have repeatedly turned to the school issue, which included several aspects related to the possibility of getting a school education by Kabardians and Balkars, including at the level of aul schools. However, in 1878 and 1907. congress of entrusted drew up sentences on the abolition of aul schools. The circumstances of the adoption of these decisions and their consequences were different, and their analysis allows us to see in the discussion forms and ways of solving the school issue the features of educational practices and intellectual culture of the indigenous population of the Nalchik district. A certain evolution of the enlightenment activity of local self-government is revealed, explained by the increased access of Kabardians and Balkars to education, cultural and treger initiatives of regional authorities and representatives of the national intelligentsia. At the same time, the limited possibilities of local education, first of all, of its initial stage – aul schools, appeared due to difficulties in mastering the Russian-language curriculum, lack of educational practices in the native language, as well as prejudices of the traditional ethno-confessional environment, focused on isolation and rejection of cultural innovations, represented by threats of traditionalist sociocultural self-organization. The consolidation of the differentiation of educational strategies of a small educated part of society with an uneducated majority contributed to the growth of cultural distances within ethnic communities and the persistence of difficulties in overcoming them. Trusted congresses, regularly making decisions on co-financing the education of Kabardians and Balkars at educational institutions in Nalchik or outside the district, but only occasionally addressing the problems of aul schools, did not contribute to resolving the revealed contradictions.